Application of novel Fe3O4/Zn-metal organic framework magnetic nanostructures as an antimicrobial agent and magnetic nanocatalyst in the synthesis of heterocyclic compounds - Bashar, Bashar S.; Kareem, Hawraa A.; Hasan, Yaser Mohamed; Ahmad, Nafis; Alshehri, A. M.; Al-Majdi, Kadhum; Hadrawi, Salema K.; AL Kubaisy, Munthir Mohammed Radhy; Qasim, Maytham T. (Frontiers in Chemistry, 2022)
By using microwave assisted, novel Fe3O4/Zn-metal organic framework magnetic nanostructures were synthesized and its crystallinity, thermal stability, adsorption/desorption isotherms, morphology and size distribution, magnetic hysteresis were characterized by XRD pattern, TGA curve, BET technique, SEM image and VSM curve, respectively. After confirming the Fe3O4/Zn-metal organic framework magnetic nanostructures structure, its antimicrobial properties against Gram-positive bacterial, Gram-negative bacterial and fungal strains, were studied based on MIC and MBC value. Examining the results showed that the high specific surface area of Fe3O4/Zn-metal organic framework magnetic nanostructures caused the antimicrobial power of nanoparticles to be high and also the observed antimicrobial effects were higher than some known commercial antimicrobial drugs. Another advantage of the specific surface area of Fe3O4/Zn-metal organic framework magnetic nanostructures was its high catalytic properties in the three-component reaction of isatin, malononitrile and dimedone, and new Spiro[indoline-Pyranopyrimidines] derivatives were synthesized with high efficiency. The results of investigating the catalytic properties of Fe3O4/Zn-metal organic framework magnetic nanostructures showed that, in addition to recyclability, derivatives can be synthesized in less time than previously reported methods. As a final result, it can be concluded that the microwave synthesis method improves the special properties of magnetic nanostructures, especially its specific surface area, and has increased its efficiency.